Peran Strategis Bahasa Indonesia dalam Implementasi Kurikulum Merdeka di Sekolah Dasar - Mulawarman, Widyatmike Gede; Hidayanto, Dwi Nugroho; Sulistyowati, Endang Dwi; Triwahyuningsih, Triwahyuningsih; Sari, Mwar; Hakiki, Dwi Rijaya (Communio: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service activity aims to examine the strategic role of the Indonesian language in the implementation of the Merdeka Belajar concept in the elementary school environment of Berau Regency. The primary targets of this activity are elementary school teachers in Berau Regency. The methods used in this activity include workshops, training, consultations, and the development of training materials. Guidance from the PkM Team contributes significantly by providing information, strategies, and approaches that support teachers in using proper Indonesian. Additionally, this PkM initiative enhances collaboration between schools, parents, and other relevant parties in efforts to ensure clarity and fluency in communication through the Indonesian language, helping create an academic environment conducive to the exchange of thoughts and ideas. This community service activity has made a significant contribution to the ability to use the Indonesian language well, not only supporting effective communication among school stakeholders but also facilitating a more inclusive and participatory learning process.